2018
DOI: 10.1002/jcb.27270
|View full text |Cite
|
Sign up to set email alerts
|

GW0742 activates peroxisome proliferator‐activated receptor δ to reduce free radicals and alleviate cardiac hypertrophy induced by hyperglycemia in cultured H9c2 cells

Abstract: Peroxisome proliferator-activated receptor δ (PPARδ), the predominant PPAR subtype in the heart, is known to regulate cardiac function. PPARδ activation may inhibit cardiac hypertrophy in H9c2 cells while the potential mechanism has not been elucidated. Then, H9c2 cells incubated with high glucose to induce hypertrophy were used to investigate using GW0742 to activate PPARδ. The fluorescence assays were applied to determine the changes in cell size, cellular calcium levels, and free radicals. Western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Following our previous report 46 , we estimated the mRNA level of each signaling target gene in current study. Briefly, TRIzol reagent (Invitrogen, Carlsbad, CA, USA) is applied to extract the total RNA from cell lysates.…”
Section: Methodsmentioning
confidence: 99%
“…Following our previous report 46 , we estimated the mRNA level of each signaling target gene in current study. Briefly, TRIzol reagent (Invitrogen, Carlsbad, CA, USA) is applied to extract the total RNA from cell lysates.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycaemia is important in the pathogenesis of diabetic disorders, and lung injury by hyperglycaemia has been demonstrated in diabetic rats [7]. However, damage to the heart by hyperglycaemia is less common, except for cardiac hypertrophy [8].…”
Section: Introductionmentioning
confidence: 99%
“…This antioxidant activity of PPARδ is directly linked to the inhibitory effect on hypertrophy of vascular smooth muscle cells stimulated by Ang II [ 28 ]. In fact, multiple studies have demonstrated that pharmacological activation of PPARδ by specific ligands can improve cardiac hypertrophy in cellular and animal models through mechanisms not yet fully elucidated [ 13 , 29 , 30 , 31 ]. By contrast, other reports have demonstrated that inducible conditional expression of PPARδ in cardiac endothelial cells leads to rapid cardiac angiogenesis and growth, including increased cardiomyocyte size [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we previously demonstrated that ligand-activated PPARδ counteracts ROS production in vascular cells to inhibit cellular senescence induced by Ang II [ 9 ]. It has also been demonstrated that PPARδ activation inhibits cardiac hypertrophy induced by Ang II and hyperglycemia through suppression of the intracellular Ca 2+ signaling pathway and free radical production in cultured H9c2 cardiomyocytes [ 12 , 13 ]. Based on its ability to protect the cardiovasculature [ 8 , 9 , 10 , 11 , 12 ], investigating the potential mechanisms of PPARδ in the development of cardiac hypertrophy could prove fruitful from a therapeutic perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation